Interdialytic weight gain and associated factors in patients undergoing hemodialysis treatment - Danielle Cristina Guimarães da Silva; Joice Natielle Mariano de Almeida; Thailane Carvalho dos Santos; Ellen de Souza Almeida; Janniny Vanderley de Souza; Amanda de Oliveira Santana (Universidade do Estado do Rio de Janeiro, 2021)
Objective: Estimate the prevalence of interdialytic weight gain (IDWG) and assess its correlation with sociodemographic, anthropometric, clinical, and biochemical indicators in patients undergoing hemodialysis. Methods: A cross-sectional study was carried out with adult and elderly patients of both sexes referred to a hemodialysis center. Data collection consisted of the application of a structured questionnaire, measurement of anthropometric parameters, and analysis of medical records. Associations between variables were assessed using simple and multiple linear regression models. Data analysis was performed using Stata 13.1 software. Results: A total of 123 patients were evaluated, the majority of which were male (63.4%), aged over 40 years (66.6%), and of low socioeconomic status (50.4%). The prevalence of excessive IDWG among study participants was 10.5% and was negatively associated with increased age (β = −0.019; 95% CI: −0.037; −0.006). Positive associations were observed between IDWG and increased waist circumference (β = 0.022; 95% CI: 0.003; 0.041), hemodialysis treatment time (expressed in months) (β = 0.017; 95% CI: 0.009; 0.026), and increased serum creatinine concentration (β = 0.091; 95% CI: 0.016; 0.166). Conclusion: It was found that IDWG was greater in younger patients and was positively associated with waist circumference, hemodialysis treatment time, and serum creatinine concentration. These findings demonstrate the importance of multi-professional interventions to improve the quality of life of patients undergoing hemodialysis.